Kurdish Students’ Pronunciation Errors due to Phoneme-Grapheme Mismatches at University Level - Rese: Arsalan Ibrahim Sulaiman; Asst.Prof.Dr. Asmaa Y. Qassim (Journal of College of Education, 2026)
One of the most important parts of foreign language teaching and learning is English pronunciation since it affects students’ communicative competence. The current study aimed to identify the most common pronunciation errors made by Kurdish students in the production of English vowels and sounds. The current study was a quantitative one and it examined 25 Kurdish third-year English department students at the College of Basic Education-English Department, University of Duhok. The number of the words was 26 contained some vowels and consonants. The data were collected by an oral pronunciation test in which students read certain words and their voices were recorded. The results showed that Kurdish students found it difficult to learn true pronunciation because the voiced /ð/ sound was harder to master than the voiceless /θ/ sound. In addition, the pronunciation of the "ou" and grapheme became inconsistent when students heard it in words such as "plough" and "thought". The students faced additional pronunciation difficulties with “ea” because of sounds that were irregular such as when pronouncing "hearth" along with "breathe" and problems with both "-ed" and "-s”. This affected their ability to master past tense and plural forms. These problems require students to receive specific phonological training that addresses their needs.
Keywords: Kurdish students, Pronunciation errors, Phoneme-grapheme Mismatches, Oral Pronunciation Test